WOMEN'S FIQH JIHAD IN CURRENT TIMES FROM THE PERSPECTIVE OF ISLAMIC RULINGS - Muhd Imran Abd Razak; Nurhidha Irawaty Kasmaruddin; Mohd Anuar Ramli; Paiz Hassan; Mohd Farhan Abd Rahman (Journal of Islamic, Social, Economics and Development, 2023)
The term jihad is often exploited by extremist groups or misunderstood by liberal groups, resulting in a negative portrayal of jihad and contributing to Islamophobia. This study aims to analyze the fiqh (Islamic jurisprudence) of jihad, specifically in the contemporary context involving women. A qualitative method is used in this study, with a content analysis approach to relevant literature on jihad and discussions by past and contemporary Islamic scholars. The findings indicate that the fiqh of jihad for women has different characteristics and requirements than that for men. The discussion of fiqh of jihad for women prioritizes the issue of the welfare of that group. Although the fiqh of jihad is based on ijtihadiyyah, it takes into account issues of nature, ability, context, and priority in determining its rulings. In this regard, a thorough examination of the benefits and harms of women's involvement in security careers such as police and military, as well as in the battlefield, must be conducted before deciding on their involvement. With proven and significant military training, the law regarding women's involvement in the battlefield can be reconsidered if the situation calls for it.